Crosstalk noise reduction in synthesized digital logic circuits. - Milter, O. (IEEE Transactions on VLSI systems)
As CMOS technology scales into the deep submicrometer regime, digital noise is becoming a metric of importance comparable to area, timing, and power, for analysis and design of CMOS VLSI systems. Noise has two detrimental effects in digital circuits: First, it can destroy logical information carried by a circuit net. Second, it causes delay uncertainty: Non critical paths might become critical because of noise. As a result, circuit speed becomes limited by noise, primarily because of capacitive coupling between wires. Most design approaches address the crosstalk noise problem at the layout generation stage, or via postlayout corrections. With continued scaling, too many circuit nets require corrections for noise, causing a design convergence problem. This work suggests to consider noise at the gate-level netlist generation stage. The paper presents a simplified analysis of on-chip crosstalk models, and demonstrates the significance of crosstalk between local wires within synthesized circuit blocks. A design flow is proposed for automatically synthesizing CMOS circuits that have improved robustness to noise effects, using standard tools, by limiting the range of gate strengths available in the cell library. The synthesized circuits incur a penalty in area/power, which can be partially recovered in a single postlayout corrective iteration. Results of design experiments indicate that delay uncertainty is the most important noise-related concern in synthesized static CMOS logic. Using a standard synthesis methodology, critical path delay differences up to 18% of the clock cycle time have been observed in functional blocks of microprocessor circuits. By using the proposed design flow, timing uncertainty was reduced to below 3%, with area and power penalties below 20%.